2021
DOI: 10.1017/dmp.2021.81
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Bias in State Triage Protocols Toward Populations With Intellectual Disabilities During the COVID-19 Pandemic

Abstract: Individuals with intellectual disabilities face discrimination on a daily basis. The COVID-19 pandemic has highlighted the systemic ableism that is embedded within American culture, particularly through healthcare bias and discrimination. In turn, this creates further marginalization during diagnosis, triage, and treatment of the novel coronavirus. Multiple states have filed complaints against state triage protocols that suggest an abled life is more worthy than a life with a disability. Although many of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…More broadly, the continued exclusion of people with disabilities in clinical trials has yet to be addressed. Rulings from the US are currently pending on some of these issues and others may follow ( Department of Health and Human Services, 2021 ; Felt et al, 2021 ). The fact that only one third of family members in the present study reported satisfaction with the support received by their family member with IDD during the pandemic may translate into legal action post-pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More broadly, the continued exclusion of people with disabilities in clinical trials has yet to be addressed. Rulings from the US are currently pending on some of these issues and others may follow ( Department of Health and Human Services, 2021 ; Felt et al, 2021 ). The fact that only one third of family members in the present study reported satisfaction with the support received by their family member with IDD during the pandemic may translate into legal action post-pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns were expressed regarding the challenges of testing people with IDD, and whether adequate support was provided to enable persons with IDD understand and communicate symptoms ( Sulkes, 2020 ), with some commentators calling for a ‘higher index of suspicion’ of symptoms being necessary for those with IDD ( Tenenbaum et al, 2021 ). Triage protocols have been found to exclude people with IDD based on disability rather than risk, a practice which resulted in investigations following complaints being filed in numerous US states ( Department of Health and Human Services, 2021 ; Felt et al, 2021 ). Concerns have also been expressed regarding the availability of accommodations for individuals with IDD who may be hospitalised for COVID-19, notably whether a caregiver was permitted to accompany the individual or was deemed a ‘visitor’ ( Margolis, 2021 ; MacGregor, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many individuals with disabilities experience discrimination in healthcare and community settings. [21][22][23] Research demonstrates that HCPs view people with ID as having a worse quality of life (QOL) than non-disabled people. 8,[24][25][26] Such assumptions have devastating impacts on the healthcare provided to this population.…”
Section: Tip #3: Unconscious Bias and Discrimination Toward Individua...mentioning
confidence: 99%
“…The study also adds novel empirical evidence around how ableism impacts COVID-19 care for people with disabilities. Concerns have been raised that state triage protocols leave opportunities for providers to be discriminatory or biased to people with disabilities [ 49 , 50 ], and media has documented anecdotal stories of patients with disabilities experiencing discrimination [ 51 ]. The findings of the current study confirm that providers’ ableist bias can result in negligent care practices; this was evident in participants’ descriptions of situations where providers skipped critical care due to their beliefs that people with disabilities have a lower quality of life and thus a life less worth living.…”
Section: Discussionmentioning
confidence: 99%